Characteristics of carbon incorporated BN films deposited by radio frequency PACVD - Kim, HS; Choi, IH; Baik, YJ (ELSEVIER SCIENCE SA, 2000)
The boron nitride (BN) and carbon incorporated BN films were deposited on Si substrates by capacitively coupled radio frequency plasma assisted chemical vapor deposition (r.f. PACVD). Deposition temperatures were varied from room temperature to 500 degreesC while deposition pressure and substrate bias were kept at 2 Pa and -500 V, respectively. BCl3 and NH3 were chosen as source gases and Ar gas was used as a carrier gas. The ordering of atomic bonds and stability of films in the ambient condition were varied with substrate temperatures. Especially, the characteristic of B-C-N chemical bonds was found to be influenced by deposition temperatures. The films deposited at room temperature were chemically very unstable. But the BN and carbon incorporated films deposited above 300 degreesC were stable. The origin of the stability was discussed with a viewpoint of the bonding characteristics of the films. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: BORON-NITRIDE; THIN-FILMS; STABILITY; NITROGEN; PHASE; BC2N